Implementation of Halal Standards to Strengthen Global HalalMarket and International Trade - Rojak, Jeje Abdul; Darmawan, Didit; Jahroni (Journal of Social Science Studies, 2021)
The development of the global halal market requires the harmonization of halal standards to facilitate smoother international trade. The main challenge in implementing halal standards is the differences in regulations and interpretations between countries. This creates obstacles for business people who want to access international markets. Disparities in certification procedures, inconsistent institutional oversight, and a lack of transparency in the certification process are major issues. Efforts are needed to harmonize halal standards internationally, including the establishment of a global certification institution with universal authority. The use of technologies such as blockchain can also improve transparency and efficiency in the halal certification process. Increased cooperation between countries in the supervision of halal products and monitoring of products circulating in international markets is also important to maintain the integrity of the halal market. These measures can reduce existing barriers and enable the global halal market to develop more effectively, benefiting both producers and consumers. A well-integrated halal market can strengthen international trade and increase the potential of the growing halal market worldwide.